Collective Property in Marriage According to Legislation and its Implementation in Jurisdictions - Orba Susilawati (UIN Sunan Gunung Djati Bandung, 2019)
The background of this research is that it begins with the lack of clarity regarding the boundaries and scope of joint assets mentioned in Law Number 1 of 1974 concerning Marriage and Presidential Instruction Number 1 of 1991 concerning Compilation of Islamic Law (hereinafter referred to as KHI). The definition of joint assets in the aforementioned regulation when correlated in different cases in religious courts there is friction in legal norms, it may even be a clash of principles, so that in the practice of dispute resolution in religious courts it creates disparity in decisions. The results showed that: Efforts to resolve the distribution of assets with husband and wife after divorce according to statutory regulations-the law and its implementation in the Court Decision in the DKI Jakarta High Court Area, the Judge decides the case by following the Islamic Law Compilation, namely ½ there is also a different division.